2022
DOI: 10.3389/fneur.2022.926130
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Hand Section of Fugl–Meyer Assessment and Motor Activity Log in Action Research Arm Test in People With Stroke

Abstract: Background:Recent findings of clinical studies have demonstrated a significant positive relationship between Fugl–Meyer Assessment of upper extremity score and the action research arm test (ARAT) score in people with stroke. Although the motor activity log (MAL) can assess the self-perception of motor performance, which can affect the performance of the upper limb, the relationship between MAL score and ARAT score still remains unclear. The objective of this study is to quantify the independent contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Although the FM scale is not related to viscoelastic properties, the correlation was significant with the MAS (r = 0.89, p = 0.012). Thus, the values found in our study corroborate the literature, as well as correlate with the FM scale, in that using the less-affected limb tends to predict low functionality performance [ 22 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the FM scale is not related to viscoelastic properties, the correlation was significant with the MAS (r = 0.89, p = 0.012). Thus, the values found in our study corroborate the literature, as well as correlate with the FM scale, in that using the less-affected limb tends to predict low functionality performance [ 22 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…The quantitative domain involves scores ranging from zero (“does not use the most affected upper limb”) to five (“uses the most affected upper limb the same way as before the stroke”). In the qualitative domain, the variation in scores ranges from zero (“the most affected upper limb is not used at all for the activity”) to five (“ability to use the most affected upper limb is as good as it was before the stroke”) [ 22 ]. The total score of the scale is calculated by summing the averages for each of the subscale categories.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical characteristics of patients according to ARAT severity classifications are presented in Table 2. The total ARAT scores (median [first to third quarter]) before treatment were 4 [3,6] in the No recovery group, 16 [13,18] in the Poor recovery group, 30 [26,36] in the Limited recovery group, 48 [45,51] in the Notable recovery group, and 57 [56,57] in the Full recovery group. The JASMID quantity and quality scores were the highest in the Full recovery group and the lowest in the No recovery group.…”
Section: Outcome Datamentioning
confidence: 99%
“…Since the ARAT consists of object manipulation and reaching tasks, the occupational therapist (OT) plans exercises by estimating the ADLs in which the patient can use their hands based on the obtained assessment results. Since the ARAT score correlates with the Motor activity log, which investigates the use of the paralyzed limb in ADLs, OTs who help patients improve their activity limitations can use the score as a reference value for the content of exercises and goal setting [18,19]. If ARAT scores are predicted to improve with NEURO, it will be easier for OTs to pre-determine the content of ADL exercises and develop goals for ADLs that patients can achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the motor activity log (MAL) scale correlates directly with both the ability to manipulate objects and the perceived ability to use the affected limb [ 20 ]. On the other hand, previous studies have revealed that the impaired motor functioning of the paretic upper limb can be quantified using the upper extremity FMA assessment (FMA-UE), correlated significantly with people with stroke and with the action research arm test (ARAT) and MAL scales [ 23 ]. However, it is important to add the measurement of QoL when dealing with patients who have just suffered a stroke, since it is intimately linked to physical and functional health.…”
Section: Introductionmentioning
confidence: 99%